Something Hidden in the Ranges : The Secret Life of Mountain Ecosystems - Wohl, Ellen E., 1962- (Book collections on Project MUSE., 2021)
"We all see the largest features of mountain ecosystems-the impressively rugged peaks, the clear blue lakes, and the extensive forests-but each of these readily visible features depends on largely invisible creatures and flows of material and energy. Something Hidden in the Ranges draws on a wide array of scientific research to reveal the complex ecology of Rocky Mountain National Park in Colorado and, by extension, of mountain ecosystems generally. Geologist Ellen Wohl has spent three decades investigating the streams and forests near her home in Colorado. In writing that is free from jargon and easy to understand, she tells the intricate story of how streams provide energy to adjacent forests, how lake sediments record the history of wind-blown pollutants, and how hidden networks of fungi keeps forests healthy. She guides readers through forests at both lower and higher elevations, revealing how trees rely on microbes in the soil, in the forest canopy, and even within individual pine needles to obtain the food they need. Other chapters focus on subalpine lakes, mountain streams, beaver meadows, and alpine tundra. While scientists, students, and scholars will benefit from Wohl's intimate knowledge of mountain ecosystems, Something Hidden in the Ranges is written for anyone interested in natural or environmental history. It will change the way readers perceive and think about natural landscapes"--